Parametric investigation of catalytic dry reforming of glycerol to synthesis gas - Bulutoğlu, Pelin Su. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Dry reforming of glycerol is a highly promising way for production of synthesis gas, as it involves catalytic conversion of CO2, a greenhouse gas that hit threatening levels, with glycerol, which is a renewable hydrocarbon that is excessively available due to increasing bio-diesel production. The reaction has started to become the focus of experimental studies only recently, and there is still a huge lack of information in the literature regarding catalysis of glycerol dry reforming. In this study, it is aimed to test and compare the activities of Rh and Co based catalysts supported on ZrO2 and CeO2 in dry reforming conditions. It is also intended to observe the e ects of two key operational parameters, namely temperature and CO2-to-glycerol (CO2/G) feed ratio, on reactant conversions and product distributions. 1 wt.% Rh/ZrO2, 1 wt.% Rh/CeO2, 5 wt.% Co/ZrO2 and 5 wt.% Co/CeO2 catalysts have been prepared and tested at temperatures between 600 and 750 C and at CO2/G ratios between 0 and 4. Characterizations of the prepared and spent catalysts were done by SEM and XRD analyses. At the studied conditions, activities of the tested catalysts were found to be decreasing in the order of Rh/ZrO2 > Rh/CeO2 > Co/ZrO2 > Co/CeO2. Rh was observed to be more active in CO2 conversion and syngas production compared to Co. On the other hand, ZrO2 supported catalysts were more selective towards H2 and CO compared to CeO2 supported catalysts. Blank tests showed glycerol conversion to some extent, suggesting that homogeneous glycerol decomposition takes place, especially at elevated temperatures. Positive e ect of temperature on reactant conversions and syngas yields was also con rmed in the activity tests. Increasing the CO2/G feed ratio resulted in inceased CO2 conversions, but H2 yields decreased with simultaneous increase in CO yields, which is attributed to reverse water gas shift reaction.
Keywords: Synthesis gas.; Hydrogen.; Carbon monoxide.